Challenges in tall building construction : speed, space and performance - Ho, Kwong Meng. (2009)
This report presents the findings of a study undertaken by the writer to examine the best construction methods as well as the best architectural and structural designs to speed up the construction of commercial tall buildings, especially in the Singapore context. The study also aims to determine the best architectural designs and structural systems to provide the maximum rentable floor areas and to evaluate the performance of buildings constructed with different structural systems and using different construction materials.